Higher Order Thinking Skill (HOTS) in Training Control Techniques Skill of Air Traffic Control Student Using Problem Based Learning Method - Fridyatama, Dimas Arya Soeadyfa (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores the use of Problem Based Learning (PBL) in air traffic control education to enhance students' control techniques skills through simulation. PBL encourages individual and group problem-solving, fostering contextual understanding. The study examines various simulation types and PBL characteristics aimed at improving these skills among air traffic control students. Results indicate that 750 students achieved an average score of 84.43, classified as very good. The research also discusses the advantages and challenges of implementing PBL in developing control techniques for air traffic control students.